2012
DOI: 10.1111/j.1753-0237.2012.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of current account balance in an oil‐rich exporting country: the case of Nigeria

Abstract: This paper examines the determinants of current accounts balance in Nigeria with emphasis on oilrelated variables using the Johansen-Julius vector error correction estimation approach, the impulse response function and the variance decomposition analysis. The results showed that oil price, oil balance and oil revenue are positively related with the current account, with only oil wealth having a significant negative impact in the long run. We find that the impact of oil price on the current balance is only sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, using the VAR method, Uneze and Ekor (2012) examined the relation between a number of oil-related variables and current account balance; and also the long-term relationship between current account balance and oil related variables between 1970 and 2008. The study revealed that oil variables play a crucial role in explaining the current account position in the long-run, while oil price was a key variable explaining current account balance in the short-run in Nigeria.…”
Section: Brief Theoretical and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, using the VAR method, Uneze and Ekor (2012) examined the relation between a number of oil-related variables and current account balance; and also the long-term relationship between current account balance and oil related variables between 1970 and 2008. The study revealed that oil variables play a crucial role in explaining the current account position in the long-run, while oil price was a key variable explaining current account balance in the short-run in Nigeria.…”
Section: Brief Theoretical and Literature Reviewmentioning
confidence: 99%
“…But on the other hand, according to Ghassan & El-Jeefri (2018), current account volatility is only influenced by local shocks. Contrary were the determinants of current account within the scope of oil-related variables, and Olumuyiwa (2008) and Uneze & Ekor (2012), find that oil price, oil revenue, and oil balance as the determinants of current account. In another study, Adegboyega et al (2019) consider the causal relationships between macroeconomic factors, demographics, and current account balances in Nigeria, and shows that causality is not caused by current account balance, but by domestic saving and investment.…”
Section: Introductionmentioning
confidence: 97%
“…The current account balance shows the ability of a country to export and import goods and services, which reflects the strength of international competitiveness and the extent to which a country can utilize its resources [2]. Overall, the current account represents the net value between the credit side (transactions that give rise to the right of residents of a country to receive payments) and the debit side (transactions that create an obligation to pay residents of a country to residents of other countries) of all transactions that recorded in the current account component system.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of trade and financial liberalisation on growth and macroeconomic variables has been extensively researched in Nigeria (Akpan, 2004;Kaita, 2015;Saifullahi and Tanimu, 2015;Danlami et al, 2018;Aigheiyisi and Isikhuemen, 2018;Apanisile and Okunlola, 2020;Aremo and Arambada, 2021;among others), little attention has been paid to unravel the impact of trade and financial liberalisation on current account balance. Several studies looked at macroeconomic and institutional factors, monetary policy, fiscal policy shock, and adjustment policy as determinants of current account (Longe, Muhammad, Ajayi and Omitogun, 2019;Danmola and Olateju, 2013;Uneze and Ekor, 2012;Oshota, 2015;Udah, 2010;Chete, 2001;Kudaisi and Olomola, 2019;Sule and Shuaibu, 2020;among others). This is surprising because trade and financial openness might have a major influence on Nigeria's current account balance especially as the country increases its trade horizon and financial sector competition.…”
Section: Introductionmentioning
confidence: 99%